Industry-Oriented Automotive Learning Model to Improve Job Readiness of Automotive Vocational School Students - bambang sudarsono (Universitas Sultan Ageng Tirtayasa, 2021)
Work readiness is a measure of the success of learning in vocational high schools (SMK). So far, the work readiness of graduates is still school-oriented, not fully in accordance with industrial needs. This study aims to produce an automotive learning model that is oriented towards industrial needs and to test its feasibility and effectiveness. The research design used was development research with 36 vocational students as subjects. The test object is the Gajah Mada Auto Service workshop and the Daihatsu International Armada Magelang. The research stage includes the development and validation stages. The development stage is to map the competencies needed by the industry and produce a learning model. The validation stage is to test the feasibility of the instrument and the effectiveness of the learning model. The research instrument used is a performance instrument that is used as a measure of the effectiveness of the model. The test results show that the industrial-oriented automotive learning model encourages disciplinary attitudes, responsibility, knowledge of the field of work and skills in the field of work very well over 70%.